Firm-Level Shocks and Labour Flows. Issue 634 (22nd July 2020) - Carlsson, Mikael; Messina, Julián; Nordström Skans, Oskar
Abstract: We analyse how labour flows respond to permanent idiosyncratic shifts in firm-level production functions and demand curves using very detailed Swedish micro data. Shocks to firms' physical productivity have only modest effects on firm-level employment decisions. In contrast, we document rapid and substantial employment adjustments through hires and separations in response to firm-level demand shocks. The choice of adjustment margin depends on the sign of the shock: firms adjust through increased hires if these shocks are positive and through increased separations if the shocks are negative.